AKTIVITAS ANTIBAKTERI AKTINOMISETES LAUT DARI PULAU ENGGANO [Antibacterial activity of marine actinomycetes from Enggano Island] - Ratnakomala, Shanti; Apriliana, Pamella; Fahrurrozi, Fahrurrozi; Lisdiyanti, Puspita; Kusharyoto, Wien (BERITA BIOLOGI, 2016)
Marine actinomycetes were isolated from mangrove sediment from the coast in Enggano, Bengkulu Province, Indonesia using the medium NBRC No. 802 modified by the addition of 2% NaCl. A total of 29 isolates of actinomycetes were isolated from three mangrove sediment samples and evaluated their potential to produce bioactive metabolites. Screening of 29 isolates marine actinomycetes isolates were performed against three bacterial pathogens had been done. Bacteria test used was Escherichia coli NBRC 14 237, Staphylococcus aureus NBRC13 276, and Bacillus subtilis NBRC 3134. Screening result showed that seven isolates have inhibitory effects against bacteria test and 22 other isolates have no inhibition. Of the seven isolates, one isolate has inhibitory effect against the growth of Gram-negative bacteria Escherichia coli, while six other isolates inhibit Gram-positive bacteria Bacillus subtilis and Staphilococcus aureus. It was concluded that, of the 29 isolates conducted in the experiment, seven isolates produce antibacterial compounds on agar medium. Molecular identification of 23 isolates were identified based on Â the gene 16S RNA sequences showed that 22 isolates belong to the genus Streptomyces and one strain belongs to the genus Dermacoccus.